Pengaruh Program Keamanan Pangan di Sekolah terhadap Pengetahuan Penjaja Pangan Jajanan dan Siswa Sekolah Dasar - Anjani Anggitasari; Winiati Pudji Rahayu; Yanti Ratnasari (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2014)
The importance of food safety education in order to improve food safety knowledge of food vendor in elementary school (ES) should not be neglected. The aims of this study were to determine the level of food safety knowledge of food vendor, the impact of food safety program on improved food understanding, and the influence of food safety education toward ES students’ knowledge. The data gained from 20 provinces in Indonesia were analyzed using SPSS using pearson analysis method and paired sample t test. The result revealed that 71.96% of food vendors possess poor knowledge, and only 28.04% had good knowledge about food safety. The result of analysis between variables showed that there was no signi cant effect of food safety programs, which were (1) the implementation of food safety regulations in school and (2) the application of food safety extension from school to food vendors. Food safety extension to ES students increased student knowledge of food safety up to 19.41%.